EFFECT OF THE FOLLICULAR DEVELOPMENT STAGE AT THE TIME OF MATING ON THE OVULATION AND EMBRYONIC SURVIVAL IN ALPACAS - Cervantes F., Miriam (2007)
The objective of this study was to evaluate the effect of the stage of the dominant follicle (df) at mating on the ovulation and embryonic survival in alpacas. A total of 116 alpacaswith ³15 day-post-partum resting period were used and evaluated by transrectal ultrasonography in order to distribute them in 4 groups: G1 (df in growing stage, diameter: 6 mm), G2 (df in growing stage, diameter: ³ 7 £ 12 mm), G3 (df in static stage, diameter: ³7 mm,) and G4 (df in regression stage, diameter: ³7 mm). Subsequently, all alpacas were mated except 5 alpacas of group G1 that rejected the male. Mating day was considered as day 0. Additional ultrasound evaluations were carried out on days 2 (occurrence of ovulation), 9 (presence and size of the corpus luteum); 20, 25, 30 and 35 (presence of embryonic vesicle or embryo). On day 15, a sexual receptiveness test was performed. Ovulationoccurredin97.3% ofalpacasthatweremated(n=111) butwithoutsignificant differences(p<0.05) betweengroups. Onday9, nosignificantdifferenceintheaverage sizeofthecorpusluteumwasobservedamonggroups. Theembryonicsurvivalratewas alsonotsignificantlydifferentamongthegroups, buttherewasatendencytoagreater rateofsurvivalforgroupG2(65.5% ) onday35aftermating. Theseresultssuggestedthat thestageoffolliculardevelopmentofthedominantfollicleduringmatingdoesnothave asignificanteffectontherateofovulationandembryonicsurvivalinalpacas.